2017
DOI: 10.1038/s41467-017-02181-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regression analysis of coordinated expression

Abstract: Co-expression analysis is widely used to predict gene function and to identify functionally related gene sets. However, co-expression analysis using human cancer transcriptomic data is confounded by somatic copy number alterations (SCNA), which produce co-expression signatures based on physical proximity rather than biological function. To better understand gene–gene co-expression based on biological regulation but not SCNA, we describe a method termed “Genomic Regression Analysis of Coordinated Expression” (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…Although in the presence of somatic copy number change we do not expect a linear correlation between copy number, mRNA or mRNA and protein expressions for all affected genes [ 23 ], the AIFM3 and DLK1 proteins’ expression increased in most MTC tissues, while their expression was absent in normal thyroid. As such, even if a change in DNA copy number is just one mechanism associated with changes in gene expression, the expression analysis allows us to demonstrate that the DLK1 copy number gain was positively correlated with protein expression, even in a nonlinear way.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the presence of somatic copy number change we do not expect a linear correlation between copy number, mRNA or mRNA and protein expressions for all affected genes [ 23 ], the AIFM3 and DLK1 proteins’ expression increased in most MTC tissues, while their expression was absent in normal thyroid. As such, even if a change in DNA copy number is just one mechanism associated with changes in gene expression, the expression analysis allows us to demonstrate that the DLK1 copy number gain was positively correlated with protein expression, even in a nonlinear way.…”
Section: Discussionmentioning
confidence: 99%
“…However, co-expression analysis results from WGCNA may be hard to interpret since copy number variant (CNV) itself is a common feature in cancer 31 . In order to adjust for the variation in gene expression contributed by CNV, we also implemented an additional co-expression analysis with GRACE 32 — a recently proposed method which removes the influence of CNV before analysis. To implement the two analyses, we selected cervical cancer patients from TCGA who had both gene expression and copy number alteration, and finally kept 34 genes of 284 patients for GRACE and 48 genes of 296 patients for WGCNA.…”
Section: Methodsmentioning
confidence: 99%
“…Three SMAD corepressors have been identified including the homeodomain protein TG-interacting factors (TGIFs), Ski, and SnoN protein [19][20][21]. We therefore examined genes that are negatively correlated with these corepressors in the TCGA data set on ccRCC [22]. Intriguingly, this analysis identified that TGIF2 is inversely correlated with the expression of genes involved in the TCA cycle enzymes.…”
Section: Hdac7 Acts As a Corepressor For Tgf-β Mediated Suppression Omentioning
confidence: 99%